Restorative Justice for Child Abortion Offenders - Mutmainnah, Luluk; Begishev, Ildar (Faculty of Law, University of Dr. Soetomo, 2024)
The application of restorative justice can only be applied in certain cases. For example, cases involving children are explicitly explained in Article 1 point (6) of Law Number 11/2012 concerning the Juvenile Justice System. Then, what about the child as the perpetrator of abortion who has eliminated the life of his flesh and blood, whether restorative justice can be applied. This study aims to examine the restorative justice approach in the criminal justice system and the punishment of children who commit abortion based on restorative justice. The method used in this research is normative legal research, with statutory, and conceptual approaches. The results showed that restorative justice approach in the criminal justice system can be applied to certain cases. For example, corruption, narcotics, children and so on. While the punishment of abortion offenders based on restorative justice is not necessarily applicable. This is because not all abortions are performed by rape victims.